DEMOGRAPHIC DETERMINANTS AND ENTREPRENEURIAL MINDSET: A STUDY ON WOMEN ENTREPRENEURS AND THEIR BUSINESS OUTCOMES. - Devi, Thokala; Bindu, V. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
It focuses on how personal and social factors like age, education, caste, marital status, and economic background influence women’s capacity to think, act, and succeed as entrepreneurs. The title reflects the dual emphasis of the study: identifying the key demographic influences and analyzing how these shape women's entrepreneurial thinking and performance. It also hints at the goal of understanding the broader business outcomes emerging from these interactions. The study aims tohighlight the importance of tailored support mechanisms to help women entrepreneurs thrive in diverse socio-economic settings. This study critically examines how various demographic factors affect the entrepreneurial mindset of women and how these, in turn, influence their business outcomes. Focusing on women from different social backgrounds, the research investigates how their circumstances either enable or restrict their entrepreneurial activities. The study employs both quantitative and qualitative methods to analyse data collected from a diverse sample of women entrepreneurs. Key areas explored include access to resources, decision-making power, risk- taking behavior, innovation, and overall business performance. Ultimately, the research offers insights that can support policy recommendations aimed at enhancing women's participation in entrepreneurship and improving their chances of long-term business sustainability.